LA INVESTIGACIÓN EN LAS UNIVERSIDADESARGENTINAS Y SU EVALUACIÓN - Dávila, Mabel; Guaglianone, Ariadna (European Scientific Journal, ESJ, 2014)
This paper presents a study made on the research policies adopted in Argentine universities and their evaluation. A documentary analysis on current regulations, impact assessments and interviews to key persons enabled to reconstruct the principal aspects of the processes of research development in each country, especially in universities and their evaluation systems. The comparison allows for identifying, among the common aspects, the difficulties in developing a quality evaluation process considering the diversity found in higher education heterogeneous systems. Likewise, there exist differences related to the origin and consolidation of the systems evaluating university quality and science and technology, the policies developed in different stages and the influence exerted by the political and economic context.